Contribution of medical affairs to an efficient management in the pharmaceutical industry - Dias, José Augusto Aleixo (2019)
During the last decade the pharmaceutical industry (PI) operations became far more complex due to several structural and organizational changes, new legislation and pharmacoeconomic constraints. The role of Medical Affairs (MA) has been increasingly important and the interactions between PI and healthcare professionals (HCP) are currently much more based on science, than in marketing or commercial arguments. This thesis provides an in-depth description of the MA function, maps key areas of activity, challenges processes and opportunities, based on the feedback collected from PI professionals, HCP, regulatory authorities, payers and patient´s associations, while suggesting metrics to evaluate the activity and impact of such actions. To collect insights from these sources two questionnaires were sent to 400 pharmaceutical industry professionals and to 197 customers, addressing the most relevant topics of the MA contribution to strategic and operational activities, while identifying areas where there was greater perceived value of their activity. There were 169 responders to the first survey (colleagues), while 40 answers to the second one (customers). The importance of the MA on the overall results of the company was very high rated and, its contribution to strategic activities was seen as essential for the support of product launch, improvement of therapeutic adherence and partnerships with Patient’s Associations. Higher scores were also given to operational activities such as medical awareness/education and symposia preparation, internal training and advisory board management. A great deal of medical effort was also spent in content creation, preparation and review of materials, in medicine related responses, presentations, reimbursement dossiers, safety risk management, internal cross functional meetings, as well as, in dealing with customers. Digital and multichannel medical labor was still rated low, while the contribution for mobile applications and similar devices gained some interest. The number of medicines considered reasonable for a Medical Affairs professional to be responsible for, was two through three. Customer facing activity was found to be reasonable up to ten customers per medical full time equivalent (FTE). MA efficiency was considered to be better exercised if office based rather than home based, while clinical research was considered to be more efficient if performed by company resources than by clinical research organizations (CRO).For these colleagues, the most important driver for clinical research in our country was said to be interest/perceived value while, long approval timelines, lack of resources and low curriculum vitae impact were identified as major roadblocks. The customer’s experience with clinical trials was greater than with investigator initiated research (IIR) or other non-interventional studies. When recruiting a Medical Affairs person, the characteristics perceived as most relevant were: a problem solving attitude, flexibility, pro-activeness and competency. The most important factors impacting Medical Affairs retention were: opportunities for personal development, recognition and work conditions. The contribution of the Medical Affairs to the reputation and credibility of the pharmaceutical industry was very highly rated. Looking at the future, most colleagues forsee a greater involvement of MA in pharmaceutical opperations. The impact of the implementation of the European Federation of Pharmaceutical Industries and Associations (EFPIA) disclosure code of ethics and transparency governing the relations between pharma industry and HCP was considered to be high, while the pharmaceutical image was assessed as good. In the future, the majority of customers foresee greater Medical Affairs involvement, while patients as well as citizens, will have a greater participation on the decision making process of their own health. At the end, set of MA metrics on volume and impact is also suggested.